2020
DOI: 10.1530/eje-19-0860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cosyntropin during adrenal venous sampling on subtype of primary aldosteronism: analysis of surgical outcome

Abstract: Objectives We investigated the clinical significance of ACTH stimulation during adrenal venous sampling (AVS) by surgical outcome of primary aldosteronism (PA). Design Multicenter retrospective study by Japan PA study. Method We allocated 314 patients with both basal and ACTH-stimulated AVS data who underwent adrenalectomy to three groups: basal lateralization index (LI) ≥2 with ACTH-stimulated LI ≥4 on the ipsilateral side (Unilateral (U) to U group, n = 245); basal LI <2 with ACTH-stimulated LI ≥4 (Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…31 In the many studies reporting an overall decrease in LI following ACTH, this corresponded to a significant decrease in actual lateralization rates compared with unstimulated values, 18,21,22,25–27 such that there can be as little as 9% and up to 40% discordance between unstimulated and stimulated lateralization rates. 18–21,26,35,36 This decrease in lateralization rates with ACTH is seen regardless of the mode of ACTH administration. Data regarding the effect of ACTH on clinical outcomes are mixed, with some studies reporting no improvement of postadrenalectomy outcomes with ACTH 22,26 while one found that the post-ACTH lateralization index correlated better with positive postoperative clinical outcomes than the unstimulated LI.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…31 In the many studies reporting an overall decrease in LI following ACTH, this corresponded to a significant decrease in actual lateralization rates compared with unstimulated values, 18,21,22,25–27 such that there can be as little as 9% and up to 40% discordance between unstimulated and stimulated lateralization rates. 18–21,26,35,36 This decrease in lateralization rates with ACTH is seen regardless of the mode of ACTH administration. Data regarding the effect of ACTH on clinical outcomes are mixed, with some studies reporting no improvement of postadrenalectomy outcomes with ACTH 22,26 while one found that the post-ACTH lateralization index correlated better with positive postoperative clinical outcomes than the unstimulated LI.…”
Section: Discussionmentioning
confidence: 82%
“…16,22 Based on unstimulated and stimulated discordance rates, upwards of 1/3 fewer patients would be eligible for unilateral intervention if relying solely on the post-ACTH lateralization index. 21,36 Surgical adrenalectomy is the only potentially curative procedure for primary aldosteronism and appears to have superior cardiovascular, metabolic, renal, and quality of life outcomes compared with medical therapy. 6–13,40 So as not to exclude any patients who might benefit from surgery, we underscore the recommendation that ACTH stimulation in the context of AVS be limited primarily to determination of the SI, and that the lateralization index be primarily calculated on the basis of pre-ACTH or unstimulated sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the PA subtype in the same patients demonstrated that ACTH stimulation increases the bilateral PA compared to without ACTH stimulation [113]. Effects of ACTH stimulation on the diagnostic accuracy of laterality vary from study to study: some studies demonstrated it better with ACTH stimulation [114,115], and another study showed the opposite result [116].…”
Section: Evidence and Commentsmentioning
confidence: 98%
“…We obtained data on patients who were diagnosed with PA based on the clinical guidelines in Japan and underwent adrenal venous sampling (AVS) between January 2006 and March 2019 (21,22). The PA subtype was diagnosed based on AVS with adrenocorticotropic hormone (ACTH, cosyntropin) stimulation as previously described (23). Briefly, AVS was considered successful when the selectivity index (the ratio of the cortisol concentration in the adrenal vein to that in the inferior vena cava) was >5 on ACTH stimulation.…”
Section: Study Design and Participantsmentioning
confidence: 99%